Biological AOX removal of pulp mill plant effluent by Pseudomonas Aeruginosa – Bench study - Kumar, Anil; Dhall, Purnima; Kumar, Rita (Journal of Environmental Engineering and Landscape Management, 2013)
Discharge of adsorbable organic halides (AOX) into the water bodies has resulted into many health and environmental problems such as endocrine disruption, aquatic toxicity, bioaccumulation and carcinogenicity. The already known physical, chemical and electrochemical methods are not economically viable for the control of water pollution. So this paper focuses on the biological reduction of AOX from pulp and paper mill effluent using isolated bacteria. The isolated bacteria were screened and finally Pseudomonas aeruginosa strain 1 was used further. The effect of various parameters such as, bacterial cell concentration, surface washing of bacterial cell and agitation were investigated and it was found that to some extend every parameter has resulted in the reduction of AOX from the effluent. It was inferred that the three time washed pellet inoculated in the ratio of 1:1 (sample: pellet) and incubated at 150 rpm at 37°C for 24h has resulted in 78% of AOX removal.